Pengaruh Penerapan Metode Curah Pendapat Terhadap Hasil Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas VII SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Octania Simangunsong; Rida Gultom; Ronny Simatupang; Risden Anakampun; Taripar Aripin Samosir (Jurnal Pendidikan Agama dan Teologi, 2023)
The aim of this research is to find out the learning outcomes of students' Christian Religious Education and Character Education which are taught using the brainstorming method are higher than those taught using the problem solving method in class VII at SMP Negeri 1 Sipoholon in the 2023/2024 academic year. The method used in this research is true experimental design with posttest only control type. The population is all class VII students of SMP N 1 Sipoholon for the 2023/2024 academic year, totaling 189 people. The sample was determined using a purposive sampling technique of 62 people with conditions set in class VII-3 as the experimental class and class VII-4 as the control class. Data was collected with a test of 30 question items. The test data were analyzed using the separated variance t test formula according to the test analysis requirements, namely n1=n2 and the variance of the two sample groups was homogeneous. The results of hypothesis testing obtained a value of tcount = 11.13> ttable (α = 0.05; dk = n1+n2-2= 60) = ttable 1.671, so H₀ is rejected and H1 is accepted. Based on the research results, it can be seen that using the brainstorming method with an average learning achievement score of 8.26 is higher than using the problem solving method with an average score of 5.09 in class VII of SMP Negeri 1 Sipoholon for the 2023/2024 academic year.